THE SEMANTIC RELATIONSHIP BETWEEN ×™Ö°×¨Ö»×©Ö¸Ö¼××” AND × Ö·×—Ö²×œÖ¸Ö¼×” - van Aarde, Tim (Journal for Semitics, 2017)
In almost every case except late usage the word group ×™Ö°×¨Ö»×©Ö¸Ö¼××” and its derivatives refer to taking possession of the object named. The word group × Ö·×—Ö²×œÖ¸Ö¼××” and its derivatives refer to the inheritance of household property. In late usage ×™Ö°×¨Ö»×©Ö¸Ö¼××” and × Ö·×—Ö²×œÖ¸Ö¼××” share the semantic field of inheritance and have been considered to be synonymous. This interpretation is critically re-evaluated. The word group × Ö·×—Ö²×œÖ¸Ö¼××” has the meaning of permanent possession of the inheritance of the familyâ€™s wealth and ×™Ö°×¨Ö»×©Ö¸Ö¼××” the possession of property involving acquisition without stipulating the mode of acquisition. The continued possession of the land, ×™Ö°×¨Ö»×©Ö¸Ö¼××” , was dependent upon the covenant relationship with Yahweh and although the possession of the land could be lost the land was allotted as a permanent possession, × Ö·×—Ö²×œÖ¸Ö¼××” , to the household clans and tribes of Israel and restoration made on the grounds of the rights of inheritance. Land was the centre of the social system of Israel and it was the abuse of the rights associated with land that reflected a breakdown in the covenant relationship with Yahweh. A comparison is made of Jeremiah 32 and Ruth 4 in terms of the relation of ×™Ö°×¨Ö»×©Ö¸Ö¼××” and × Ö·×—Ö²×œÖ¸Ö¼××” to kinsman-redemption which was central to Israelâ€™s social system.